211k views
15 votes
Given f(x) = 3x2 + 7x - 3 and f(x) = 8x – 5, find (f - g)(4).

User Fabjan
by
6.0k points

1 Answer

7 votes

Answer: (f-g)(4)=46

Explanation:

(f-g)(4) means f(4)-g(4). We first need to find the values of f(4) and g(4).

f(4)=3(4)²+7(4)-3 [exponent]

f(4)=3(16)+7(4)-3 [multiply]

f(4)=48+28-3 [add]

f(4)=76-3 [subtract]

f(4)=73

g(4)=8(4)-5 [multiply]

g(4)=32-5 [subtract]

g(4)=27

Now that we have the value for f(4) and g(4), we can subtract them.

73-27=46

(f-g)(4)=46

User Ajzeffer
by
6.0k points